Pesan Teologis Nubuat Nabi Amos dalam Perikop Nubuat Hukuman atas Bangsa-Bangsa (Am 1:3-2:16) dan Relevansinya bagi Hubungan Antara Agama - Silvester Manca (STIPAS St. Sirilus Ruteng, 2021)
This article analyses theological messages of Amos’ prophecy in thepassage of the Prophecy of the Punishment upon the Nations and itsrelevance to the relationship between religious communities. By using themethod of literature study, the author reveals a number of theologicalmessages in the passage, namely Yahweh is the God of all nations, Godupholds human dignity, and Israel’s responsibility as chosen nation. Theauthor also describes the relevance of these theological messages in thecontext of the relationship between religions. Thus, it is hoped that theriches of biblical traditions will inspire adherents of religions, especiallyChristians, to build a constructive relationship with adherents of otherreligions and beliefs in order to achieve world peace.